Neuroprotective Effects of Pyruvate Following NMDA-Mediated Excitotoxic Insults in Hippocampal Slices - Izumi, Yukitoshi (2010)
The activation of N-methyl-D-aspartate (NMDA) receptors and subsequent release of nitric oxide (NO) are likely contributors to the delayed neuronal damage that accompanies ischemia and other neurodegenerative conditions. NMDA receptor antagonists and inhibitors of NO synthesis, however, are of limited benefit when administered following excitotoxic events, suggesting the importance of determining downstream events that result in neuronal degeneration. Inhibition of glyceraldehyde-3-phosphate-dehydrogenase (GAPDH), a key glycolytic enzyme, which may result in glycolytic impairment, is one of the biological targets of NO. This suggests that alternative energy substrates may prevent neuronal damage. Using rat hippocampal slices from juvenile rats, we examined the role of glycolytic impairment in NMDA mediated excitotoxicity and whether pyruvate, an end product of glycolysis, prevents the excitotoxic neuronal injury. We observed that administration of NMDA acutely depresses ATP levels and result in a slowly developing inhibition of GAPDH. Unlike NMDA receptor antagonists or NO inhibitors, exogenously applied pyruvate is effective in restoring ATP levels and preventing delayed neuronal degeneration and synaptic deterioration when administered in the period following NMDA receptor activation. This raises the possibility that treatment with agents that maintain cellular energy function can prevent delayed excitotoxicity.